Antihyperuricemia Potential in Ethanol Extract of Siamese Bamboo (Thyrsostachys siamensis) Leaves on Male White House Mice (Mus musculus L.) - Muhamad Aditya Hidayah; Gerda Pintoko Tunjungsari; Retno Aliyatul Fikroh; Hisyam Mashadi; Titik Handayani; Beta Achromi Nurohmah (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Hyperuricemia is commonly treated with the synthesis drug allopurinol. Allopurinol lowers uric acid by inhibiting the enzyme xanthine oxidase but provides side effects on the skin and kidneys. In addition, it can be overcome with secondary metabolite compounds in plants. This compound is found in bamboo leaves that have long been used by Chinese people for treatment. This study aims to find out the ability of siamese bamboo leaf extract (Thyrsostachys siamensis) in lowering the uric acid levels of white house mice. Fine siamese bamboo leaves are extracted using 70% ethanol and then evaporated with a rotary evaporator. Obtained a viscous extract with a yield of 55.42% which was further analyzed the phytochemical content and obtained that siamese bamboo leaf extract contains alkaloids, flavonoids, saponins, tannins, and triterpenoids. The ability to reduce uric acid levels was tested in male white house mice (Mus musculus L) with six treatment groups, namely group I (without treatment), group II (negative control), group III (positive control), group IV (extract 5 mg / 20 g WW), group V (extract 10 mg / 20 g WW, group VI (extract 20 mg / 20 g WW) which had previously been adapted in the test cage environment. Tests of the activity of siamese bamboo leaf ethanol extract (Thyrsostachys siamensis) against the reduction of white house mouse uric acid showed the best percentage reduction at an extract dose of 5 mg / 20 g BB of 65.85%. This value does not differ much and is comparable to the decrease by allopurinol 0.78 mg / 20 g BB of 58.97%. Therefore, siamese bamboo leaves (Thyrsostachys siamensis) proved effective in lowering uric acid levels. This proves that siamese bamboo leaves can lower the uric acid levels of white house mice and have the potential to be used as a treatment material for hyperuricemia and is expected to provide information on the use of bamboo plants (Thyrsostachys siamensis) as a lowering of uric acid levels. The results of this uric acid reduction test can be used as a reference to determine how to consume bamboo leaf extract (Thyrsostachys siamensis) for the treatment or prevention of gout.